New records of water mites (Acari: Hydrachnidia) from interstitial freshwaters of India, with descriptions of three new species - Pesic, Vladimir; Reddy, Yenumula Ranga (Zootaxa, 2009)
New records of six water mite species (Acari: Hydrachnidia) from interstitial waters of India are reported; three of them, viz. Atractides panesari, Albaxona indica and Axonopsis periyar are described as new to science. Atractides gracilis Jin, 1997 is replaced with Atractides jini nom. nov. Moreover, an additional description of the female of Atractides biscutatus Cook, 1967 is given.